Primary Adrenal Lymphoma Possibly Associated With Epstein–Barr Virus Reactivation Due to Immunosuppression Under Methotrexate Therapy. Issue 31 (August 2015) - Ohkura, Yu; Shindoh, Junichi; Haruta, Shusuke; Kaji, Daisuke; Ota, Yasunori; Fujii, Takeshi; Hashimoto, Masaji; Watanabe, Goro; Matsuda, Masamichi; Perbinder, Grewal.
<x xml:space="preserve">Abstract</x> Abstract Primary adrenal lymphoproliferative disorder (LPD) is an extremely rare disease that is widely known to be associated with methotrexate (MTX) use in patients with rheumatoid arthritis (RA). A 70-year-old man was incidentally found to have a tumor at the dorsal part of the liver in a medical check-up. He had a history of RA treated with MTX. Abdominal ultrasonography demonstrated a low echoic mass (30 mm in diameter) at the dorsal part of the liver, located close to the inferior vena cava. Preoperative differential diagnoses included intrahepatic cholangiocarcinoma, adrenal tumor, and hepatic malignant lymphoma, but no definitive diagnosis was reached. On exploratory laparotomy, the tumor seemed to be derived from the right adrenal gland and adhered tightly to segment 7 of the liver. Therefore, right adrenectomy with partial resection of segment 7 of the liver was performed. Pathological findings revealed diffuse inflammatory cell infiltration with a population of small atypical lymphoid cells, with positive immunohistochemical evidence for Epstein–Barr virus (EBV). Final diagnosis was primary adrenal iatrogenic EBV-positive LPD, classified as "other iatrogenic immunodeficiency-associated LPDs: Hodgkin-like lesions." In this report, we described the possibility of the spontaneous healing of MTX-associated LPD (MTX-LPD) before treatment and the importance of doubting MTX-LPD and doing immunostaining to necrotic tissue. To our knowledge, this is the first reported case of MTX-related EBV-positive LPD, Hodgkin-like lesion, of the unilateral adrenal gland in patient with RA.